Learning From Students’ Experiences in Writing Paragraph - Moh. Yamin (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
This article aims to describe the students' ability in writing a paragraph. It is a descriptive qualitative in which the number of respondents is 60 students. All samples are taken from the guided writing class as the first subject series of a writing class. The data collection is obtained through a number of assignments they did and uploaded in a blog. From all assignments of writing task, only six assignments of writing task were taken and analyzed, based on top ones in writing quality starting from topic sentence, supporting sentences, and concluding sentence. Based on the analysis result, students’ ability is located on weakness in determining the topic sentence, starting the topic sentence, and writing supporting sentences. Their weakness appears because of the inability to formulate the topic, topic sentence, and difficulty to find the relevant supporting sentences to write for supporting the topic sentence. The inability of formulating topic, topic sentence, and supporting sentences contributes towards inability to apply the unity knowledge in making supporting sentences united.